2001
DOI: 10.1111/j.1151-2916.2001.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram Studies in the Systems La2O3–SrO–Ga2O3, La2O3–MgO–Ga2O3, and SrO–MgO–Ga2O3 at 1400°C in Air

Abstract: The ternary systems La2O3–SrO–Ga2O3, La2O3–MgO–Ga2O3, and SrO–MgO–Ga2O3 were studied at 1400°C in air, with emphasis on LaGaO3. The compound exhibited a small solid solubility of strontium substituting for lanthanum and also of magnesium substituting for gallium. In the system La2O3–SrO–Ga2O3, LaGaO3 existed only within a very narrow concentration region, whereas in the system La2O3–MgO–Ga2O3, LaGaO3 was in equilibrium with most of the phases of the system. The system SrO–MgO–Ga2O3 at 1400°C in air was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
(8 reference statements)
4
24
0
1
Order By: Relevance
“…Majewski et al reported that a liquid phase in a ternary system of SrO-MgO-Ga 2 O 3 was observed during DTA measurement. An extended and complete melting was occurred at~1,260°C and~1380°C, respectively [36]. Thus, the presence of a liquid phase can be also expected during calcination of the LSGM powder.…”
Section: Resultsmentioning
confidence: 95%
“…Majewski et al reported that a liquid phase in a ternary system of SrO-MgO-Ga 2 O 3 was observed during DTA measurement. An extended and complete melting was occurred at~1,260°C and~1380°C, respectively [36]. Thus, the presence of a liquid phase can be also expected during calcination of the LSGM powder.…”
Section: Resultsmentioning
confidence: 95%
“…The solid solubility of Ga in MgO was found to increase from 4.7 at 1673 K to 12.7 mol% Ga 2 O 3 at 1873 K The column 'Use' indicates whether the values were used (+) or not used (−) in the optimisation. [18][19][20]. A surprisingly large solubility of Mg in ␤-Ga 2 O 3 at 1673 K (11.3 mol% MgO) has been reported by Majewski and co-workers [18,19].…”
Section: The Ga-mg-o Systemmentioning
confidence: 79%
“…At 1300 K, the spinel phase exists between 47.4 and 50.3 mol% MgO [17]. Majewski and co-workers reported that the compound MgGa 2 O 4 exhibited a variable Mg:Ga ratio between 35:65 and 40:60 at 1673 K [18,19]. Both compositions are, however, on the MgO-rich side and, since the uncertainty of such measurements is unknown, a systematic error may be suspected.…”
Section: The Ga-mg-o Systemmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, at 1,673 K it takes about 250 h to equilibrate LSGM within a distance of 1 lm, i.e., a grain of 2 lm diameter or a surface layer of 1 lm thickness. In the phase diagram [ 17,18] and diffusion studies the current authors have explicitly taken care of this fact by equilibrating the samples at 1,673 K for 10 days, in contrast to previous phase diagram studies with fairly short equilibration times [46][47][48].…”
Section: General Discussion and Implications For Solid Oxide Fuel Cellsmentioning
confidence: 96%